(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A school management system is a platform designed for organizing and managing the activities of an institution. As it also helps to manage the student’s information through an online platform. The development of a Web and Mobile-Based Platform for the Prefect of Discipline was conducted for online monitoring and for online management of the student’s and faculty members’ records regarding their violations. Corresponding to that are the disciplinary actions, including the status of their cases. As well, the records will become more organized, secure, and accurate. The list of violations and accompanying disciplinary procedures will be based on the students’ handbook. The system also generates an appointment for the students and teachers using the web and mobile-based platforms. In dealing with the issue that the project team ran into, the developer team developed a system based on the client’s requirements. The project system contains a login for security so that only authorized people will access the system, a dashboard to organize the report and easily view the summary report through the charts, services for receiving complaints, an appointment for creating the scheduled appointment, real-time data reports, and records containing all the records and the status of each case. This project study will help future researchers by giving them the needed information. The study discusses the new system’s features. The Web and Mobile-based platform for Prefect of Discipline will improve the transaction from a paper-based to an online platform. In that way, it will secure the information and data from unofficial users, enable the user to complain online, allow viewing of the appointment that is also scheduled online, reduce the time to find the user’s record, and lastly, show it in real-time.